Overoptimism and the Performance of Entrepreneurial Firms - Lowe, Robert A.; Ziedonis, Arvids A. (Management Science, 2006)
Recent theoretical and empirical research on cognitive bias in decision making suggests that overoptimism critically influences entrepreneurs’ decisions to establish and sustain new ventures. We investigate whether such cognitive bias influences entrepreneurial venture performance using data on commercialization efforts for university inventions. In contrast to prior studies, our results suggest that entrepreneurial overoptimism does not appear to be the determining factor in the decision to found a firm. We do find that entrepreneurs continue unsuccessful development efforts for longer periods of time than do established firms, which is consistent with entrepreneurial overoptimism in the development of technologies with uncertain market prospects. This latter finding is also consistent with rationality-based models of decision-making behavior, however. We find that the economic returns associated with many of the technologies in our sample are realized after the start-up has been acquired by an established firm, suggesting that start-ups may serve as a transitional organizational form in the market for technology commercialization.